Business Council of Australia submission to the Emissions Trading Task Group - Business Council of Australia; Australia. Prime Ministerial Task Group on Emissions Trading (Melbourne : Business Council of Australia, 2007)
Outlines a series of principles around a 'cap and trade' scheme to tackle greenhouse emissions as part of a framework which it believes can provide the foundation for an integrated global solution to emissions reduction.
"March 2007".
Title from title screen (viewed on 17 July 2007).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.bca.com.au/Content.aspx?ContentID=100982
System requirements: Adobe Acrobat reader required to view/print pdf files.
Selected for archiving
Keywords: Emissions trading -- Government policy -- Australia; Emissions trading -- Australia; Greenhouse gases -- Environmental aspects -- Australia